Planning and the civil engineer proceedings of a joint conference of the American Society of Civil Engineers, the Canadian Society for Civil Engineering and the Institution of Civil Engineers held in Torquay 20-25 September 1981. (Thomas Telford, 1982)
Areas covered in this book include pollution, siting of power stations and large industrial plants, utilities, transportation land utilization and co-ordination of technologies.